Comprehensive material activation of concrete structures - Korobko, Oksana; Vyrovoy, Valerii; Grynyova, Iryna; Vegera, Pavlo (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
The investigation focuses on improving the mechanical properties of concrete by optimising its structural organisation through external activation using a modified electromagnetic field and internal activation with carefully selected fillers. The effectiveness of activating cement composites with fractal-matrix resonators has been demonstrated. The research examines the impact of both external and internal activation on structural changes, mechanical property indices, and the damage resistance of cement composites and concretes. It has been shown that comprehensive activation enables the control of binder setting time and concrete elasticity modulus while reducing the initial volumetric deformations of hardening systems. Additionally, it enhances crack resistance and increases concrete strength. Activation reduces initial volumetric deformations and thermal changes during hardening by 1.5-2 times, shortens the setting time by 30-90 minutes without affecting the final setting time, decreases specimen damage by up to 20%, and improves compressive strength by up to 20%. Furthermore, activation allows for precise regulation of the initial setting time within a range of 15 to 210 minutes and reduces the final setting time by 15 to 90 minutes, lowering damage from technological defects by up to 10% and increasing flexural strength by up to 40%. The increase in crack resistance and concrete strength is achieved through the internal and external introduction of optimal fillers, carefully selected based on their specific surface area and quantity, along with the application of fractal-matrix resonators.